1993
DOI: 10.1016/0266-7681(93)90029-f
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Myofibroblasts in the Dermis of Patients with Dupuytren’s Contracture

Abstract: Samples of skin and underlying cord obtained at dermofasciectomy for Dupuytren's contracture have been examined for the presence of smooth muscle alpha-actin (SM alpha-actin), a marker for myofibroblasts. 15 of the 20 samples stained positively for SM alpha-actin corresponding with areas of hypercellular Dupuytren's tissue. In 12 of these 15 samples SM alpha-actin-positive hypercellular Dupuytren's tissue extended into the dermis, in three cases reaching the epidermis. In eight samples, diffusely distributed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…The main cell type responsible for DD is thought to be the myofibroblasts that are derived from the resident fibroblasts in normal fascia [8,9]. In DD, skin overlying nodular (SON) tissue as well as perinodular fat (PNF) have been shown to be abnormal and it has been suggested that they may have a role in the pathogenesis of DD [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The main cell type responsible for DD is thought to be the myofibroblasts that are derived from the resident fibroblasts in normal fascia [8,9]. In DD, skin overlying nodular (SON) tissue as well as perinodular fat (PNF) have been shown to be abnormal and it has been suggested that they may have a role in the pathogenesis of DD [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, equations (6)- (8) imply that if c > 0 and n > 0, then m f 0, so that any pathological state with a persistent inflammatory component (indicated by c > 0) exhibits a permanent myofibroblastic profile, which is a paradigm of an important class of fibro-proliferative pathologies (Ehrlich et al, 1994;McCann et al, 1993;Murray, 1993;Rudolph and Vande Berg, 1991;Schiirch et al, 1990;Skalli and Gabbiani, 1988).…”
Section: Pathological Steady Statesmentioning
confidence: 99%
“…Second, what mechanisms might cause a fibro-proliferative disorder to partially or fully regress? The clinical occurrence, extent and permanence of regression is unpredictable and unexplained (McCann et al, 1993;Murray and Pinnell, 1992). These issues are addressed below.…”
Section: If K E Andmentioning
confidence: 99%
“…Dermal fibromatosis has been 21 demonstrated within the palmar skin of patients with both primary and recurrent Dupuytren's 22 disease [1][2][3] . Also, dermofasciectomy with full thickness skin graft (FTSG) reconstruction appears to 23 alter the course of recurrence 2,4 .…”
Section: Introduction 18 19mentioning
confidence: 99%
“…The benefit of skin excision was explained by Logan and colleagues 74 when they showed Dupuytren's fibromatosis within the dermis and epidermis of patients with 75 recurrent disease, resulting in their conclusion that the only way to adequately treat disease of this 76 magnitude was by radical excision 1,7 . Recently, our group has also shown that Dupuytren's 77 fibromatosis also exists in the skin of patients without clinically apparent skin involvement 3 .…”
mentioning
confidence: 99%